2018
DOI: 10.1891/1052-3073.29.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rental Real Estate Investors During the 2000s

Abstract: Using data from the 2001, 2004, and 2008 panels of the Survey of Income and Program Participation (SIPP), this research examines the characteristics of households that invested in rental real estate during the 2000s. Given the tumultuous real estate market during that decade, rental real estate investment was investigated during the early part of the housing market boom (2001), the height of the boom (2004), and after the market began to decline (2008). Results reveal relative stability with slight investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, more research is required to understand how clients choose between compensation models. A first step in understanding how client preferences influence advisor selection was provided by Seay et al (2017), who analyzed bivariate statistics of clients that used each compensation model. Results indicated that commission-only clients were mostly older (65 and over), relatively financially knowledgeable and confident in their knowledge about finances, and were comfortable with their decision-making as it related to investments.…”
Section: Client Preferences In Compensation Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more research is required to understand how clients choose between compensation models. A first step in understanding how client preferences influence advisor selection was provided by Seay et al (2017), who analyzed bivariate statistics of clients that used each compensation model. Results indicated that commission-only clients were mostly older (65 and over), relatively financially knowledgeable and confident in their knowledge about finances, and were comfortable with their decision-making as it related to investments.…”
Section: Client Preferences In Compensation Modelsmentioning
confidence: 99%
“…Commission-and-fee clients were relatively younger (specifically, age 18 -34), more racially diverse and were full-time workers (Seay et al, 2017). They reported the highest levels of concern about fraud and were the most likely group of clients to perform a background check on their advisor, yet they believed the fees they paid were reasonable.…”
Section: Client Preferences In Compensation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few articles address the disposition of these individual investors in terms of age, gender, and wealth (Duxbury et al 2015). In the United States, the characteristics of rental property owners remained relatively consistent during the 2000s: investors are mostly white and Asian homeowners, married individuals and households without children, in good health, and with a high net income and educational levels (Seay et al 2018). Tax incentives and the potential for high returns attract novice investors to this category, even though there may be risks involved (Seay et al 2018).…”
Section: Size and Social Compositionmentioning
confidence: 99%
“…In the United States, the characteristics of rental property owners remained relatively consistent during the 2000s: investors are mostly white and Asian homeowners, married individuals and households without children, in good health, and with a high net income and educational levels (Seay et al 2018). Tax incentives and the potential for high returns attract novice investors to this category, even though there may be risks involved (Seay et al 2018). As a consequence, "smallscale, non-professional housing investors" (Goldstein 2018(Goldstein , 1111 and "amateur investors" are increasingly involved in housing speculation (Allon and Barrett 2018).…”
Section: Size and Social Compositionmentioning
confidence: 99%